PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SQUARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS X AP1 SMK PGRI PEKANBARU - Novriana, Syuhada; ', Sakur; ', Zuhri D (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This classroom action research purpose to improve learning process and to increase mathematics achievement by applying cooperative learning model type Think Pair Square (TPS). Subjects of this research are 32 student of grade X AP1 at SMK PGRI Pekanbaru academic year 2015/2016, which consisted of 12 male students and 20 female students. This research has two cycles, which each cycle has four stages, they are planning, implementation, observation, and reflection. End of each cycles closed by daily exam. Data collection was using observation sheet and daily exam test. The action implementation in successfull if there is improvement of learning process and percentage of students who reaches Kriteria Ketuntasan Minimum (KKM) increase at daily examination I and daily examination II. The results of the research activities of teachers and students showed improvement and mathematics achievement, with the result of reflection and the implementation plan of remedial study results increase, conclusions of this research is by applying that cooperative learning model type TPS can improve learning process and improve mathematics achievement grade X AP1 at SMK PGRI Pekanbaru. Key Words : Mathematics Achievement, Cooperative Learning Model Type of Think                    Pair Square